Adsorptive Accumulation of Cd(II), Co(II), Cu(II), Pb(II) and Ni(II) Ions from Water onto Kaolinite: Influence of Acid Activation - Krishna G. Bhattacharyya; Susmita Sen Gupta (Adsorption Science & Technology)
Naturally occurring kaolinite and its acid-activated form were used to separate the toxic metal ions Cd(II), Co(II), Cu(II), Pb(II) and Ni(II) from water by adsorption. Kaolinite was treated with 0.25 M H 2 SO 4 to obtain the acid-activated form. Adsorption onto the calcined forms of the clays was influenced by pH, the solution concentration of metal ions, the amount of adsorbent employed, the interaction time and the temperature. The process followed second-order kinetics very closely. Isotherm-fitting procedures showed compliance with the Langmuir and Freundlich equations suggesting the involvement of strong interactions. The Langmuir monolayer capacity showed some increase between kaolinite and the acid-activated form [Cd(II): 9.9 and 11.4 mg/g; Co(II): 11.2 and 12.1 mg/g; Cu(II): 9.2 and 10.1 mg/g; Pb(II): 11.1 and 12.1 mg/g; and Ni(II): 10.4 and 11.9 mg/g]. The thermodynamics of the rate processes showed that the adsorption of Co(II), Cd(II) and Cu(II) ions was endothermic and accompanied by an increase in both the entropy and the Gibbs' free energy. However, in contrast, the adsorption of Pb(II) and Ni(II) ions was exothermic with a decrease in entropy and an appreciable decrease in the Gibbs' free energy. The results have established that kaolinite and its acid-activated form show a good potential as adsorbents for Cd(II), Co(II), Cu(II), Pb(II) and Ni(II) ions from aqueous media.